Cyprus : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2018)
This Selected Issues paper identifies key challenges among households in reducing nonperforming loans (NPL) further in Cyprus, namely, low repayment capacity, particularly among a certain group of debtors; and weak repayment discipline owing to strategic behavior. Despite some revival of lending activity, the role of bank credit as a funding source remains limited. External inflows, drawdown of savings, use of own funds, and unpaid debt service obligations are contributing to financing economic activities, but these sources may not be sustainable over the medium term. Addressing NPLs to lower borrowing costs and reviving credit supply will be important for supporting longer-term growth. Since 2017, bank credit has provided only a moderate amount of new financing. The reduction in credit-to-GDP ratio has been almost entirely achieved by NPL write-offs and sale or transfer of loans out of the banking system, and through denominator effect. As of 2017, credit demand appears moderately strong, in line with robust economic growth, while credit supply remains broadly unchanged, reflecting continued risk averseness by banks. These trends suggest that while deleveraging is expected to continue through clean-up of bank balance sheets, growth in credit flows (pure new loans) are likely to remain at a moderate level until NPL recovery and repayment discipline improves significantly.